2015
DOI: 10.1108/ijpdlm-12-2014-0309
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian logistics: the role of logistics service providers

Abstract: Purpose – In recent years, logistics service providers (LSPs) have become important players in the humanitarian field, providing support for NGOs and governments when they respond to major disasters. However, the academic literature on humanitarian logistics has not really explored the roles that LSPs play in relief supply chains. The purpose of this paper is to investigate the role of LSPs in humanitarian relief. Design/methodology/approach – The research uses a two-stage exploratory approach: first, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
1
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 42 publications
3
132
1
4
Order By: Relevance
“…In this paper, we focus on reducing and transferring strategies for managing in-country transportation risks. We limit our study scope to the first two categories of LSPs due to their common usage in recent humanitarian response operations [24].…”
Section: Risk Management and Humanitarian Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we focus on reducing and transferring strategies for managing in-country transportation risks. We limit our study scope to the first two categories of LSPs due to their common usage in recent humanitarian response operations [24].…”
Section: Risk Management and Humanitarian Contextsmentioning
confidence: 99%
“…In HSC literature, although very few studies can be found, LSPs has been studied within three roles in relief operations: as "members", "actors", or "tools" [24]. As "members", LSPs share their resources with HOs, transfer their knowledge, and expand their partners` network.…”
Section: Logistics Service Providers and Their Roles In Disaster Reliefmentioning
confidence: 99%
“…However, organizations are increasingly developing partnerships with suppliers (we found reference to this trend among four of the reviewed organizations) and engaging in cooperative purchasing (Pazirandeh and Herlin, 2014;Pazirandeh and Norrman, 2014). There is great potential for research to document such attempts, their challenges, and effects for logistics preparedness and 2015; Vega and Roussat, 2015) that could be used as basis for empirical studies. Vega and Roussat (2015) suggested future research on the various roles played by logistics service providers in humanitarian logistics and their effect on performance.…”
Section: A Proposed Research Agendamentioning
confidence: 99%
“…There is great potential for research to document such attempts, their challenges, and effects for logistics preparedness and 2015; Vega and Roussat, 2015) that could be used as basis for empirical studies. Vega and Roussat (2015) suggested future research on the various roles played by logistics service providers in humanitarian logistics and their effect on performance. Bealt et al (2016) concluded that there is a need to focus more on how relationships can influence ability for better preparedness and environmentally sound operations.…”
Section: A Proposed Research Agendamentioning
confidence: 99%
“…-Having access to a wide range of fleets. Other HOs can enable such access by establishing partnerships with logistics service providers (LSPs) that provide different fleet types (Vega and Roussat 2015;Baharmand et al 2017). -The number of UNWFPs' staging areas (SAs) and their geographical distribution.…”
Section: Improving the Flexibilitymentioning
confidence: 99%